The Effect of Implementing Quantum Learning Model Type TANDUR with Educandy Media on English Vocabulary Mastery - Nadia Tsamrotu Tazkiyah; Indah Nurmahanani; Primanita Sholihah Rosmana (Lembaga Bale Literasi, 2026)
This study aims to analyze the effect of implementing the TANDUR-type quantum learning model assisted by Educandy media on the English vocabulary mastery of fifth-grade students at SDN 2 Sindangkasih, Purwakarta Regency. The method used was a quasi-experimental study with a non-equivalent control group design. The sample used in this study consisted of fifth-grade Class V-B as the experimental class, comprising 25 students, and fifth-grade Class V-A as the control class, comprising 25 students. The data collection technique used was purposive sampling. The results of the study indicate that the implementation of the TANDUR-type quantum learning model assisted by the Educandy media had a 56.9% effect on English vocabulary mastery. The experimental class achieved an N-Gain score of 0.5680, which falls into the moderate category. Meanwhile, the control class achieved an N-Gain score of 0.3766, which falls into the low category. The difference in scores between the two classes indicates that the implementation of the TANDUR-type quantum learning model supported by the Educandy media is more effective in improving students’ English vocabulary mastery.